Predictors of Treatment Response Following Ultrasound-Facilitated Catheter-Directed Thrombolysis for Submassive and Massive Pulmonary Embolism: A SEATTLE II Substudy. (June 2020) - Sardar, Partha; Piazza, Gregory; Goldhaber, Samuel Z.; Liu, Ping-Yu; Prabhu, William; Soukas, Peter; Aronow, Herbert D.
Abstract : Background: Little is known about which factors predict improvement in clinical and imaging parameters among patients undergoing catheter-directed thrombolysis for submassive or massive pulmonary embolism. The identification of such predictors may allow for more appropriate patient selection for ultrasound-facilitated catheter-directed thrombolysis. Methods: We conducted a retrospective cohort analysis of patients from the SEATTLE II trial (Prospective, Single-Arm, Multi-Center Trial of EkoSonic Endovascular System and Activase for Treatment of Acute Pulmonary Embolism) to identify clinical characteristics that independently predict pulmonary artery pressures, right ventricular-to-left ventricular (RV/LV) diameter ratio, and modified Miller angiographic index following ultrasound-assisted catheter-directed thrombolysis. Eligible patients had submassive or massive pulmonary embolism and an RV/LV diameter ratio ≥0.9 on chest computed tomography. Multivariable linear regression was used to identify independent clinical predictors of each outcome. Results: One hundred fifty patients with massive (n=31) or submassive (n=119) pulmonary embolism were enrolled. Mean (±SD) baseline and postprocedure RV/LV diameter ratio, pulmonary artery systolic pressure, and modified Miller Score were 1.59 (±0.39) and 1.14 (±0.2), 51.45 (±16.0), and 37.47 (±11.9), and 23.0 (±5.7) and 15.7 (±5.9), respectively. The multivariable model adjusted R 2 for absolute change in RV/LV ratio, pulmonary artery systolic pressure, modified Miller Score was 0.71, 0.57, and 0.43, respectively. After adjusting for age, gender, and baseline RV/LV ratio, pulmonary artery systolic pressure, and modified Miller Score, patients with higher body mass index, renal or hepatic dysfunction, active smoking, or a higher baseline heart rate showed less improvement. Conclusions: Patients with more life-threatening pulmonary embolism may derive the greatest benefit from ultrasound-assisted, catheter-directed thrombolysis. Abstract : Supplemental Digital Content is available in the text.